(untitled) (Journal of Science and Technology, 2016)
The simulation of solar radiation in waste stabilization ponds is a developing tool worth studying in order to understand its effects on wastewater quality in waste stabilization ponds. Hence, the research is aimed at investigating the effect of length to width ratio (L/W) in solar enhanced waste stabilization ponds (SEWSPs) treatment efficiency. SEWSPs of varying sizes made of metallic tank with inlet and outlet valves, and a solar reflector was constructed to increase the incident sunlight intensity. Wastewater samples collected from the inlet and outlet of the SEWSPs were examined for physico-chemical and biological characteristics for a period of twelve (12) months. The parameters examined were Temperature, pH, detention time, total suspended solids, dissolved oxygen, biochemical oxygen demand (BOD5), chemical oxygen demand (COD), algae count, faecal coliform and E-Coli. The efficiencies of the SEWSPs with respect to these parameters fluctuated with width variation, with the smallest SEWSP in width giving the highest treatment efficiency. The research revealed that with the incorporation of solar radiation in WSPs, a length/ width ratio of 1:0.2 should be used in the design of SEWSPs for maximum treatment efficiency.